The risks of global heating to energy systems and energy security - Hughes, Larry; de Jong, Moniek (Sustainability, 2021)
As recent events have shown, global heating is increasing the risk to many sectors of soci-ety, from agriculture to the built environment, to transportation. The energy security of most energy systems, regardless of their size, is also at risk from the effects of global heating: The reliable supply of power to end users can be threatened by extreme weather events affecting transformers and transmission and distribution networks. It can also be a threat to generators that are vulnerable to unpredictable supplies of water, such as thermal or hydroelectric generation facilities. In this paper, we use an energy security methodology to examine some of the possible climate risks to the supply of power from hydroelectricity produced by one of western Canada’s electricity suppliers. The work is of particular interest because it shows how the increasing number of heatwaves that are affecting parts of western Canada and the Pacific Northwest could affect electricity supply in some western Canadian provinces and northern U.S. states.
Created from Fastlane, Scopus look-up
Keywords: Canada; Climate change; Climate emergency; Climate emergency; Drought; Energy risk assessment; Glaciers; Hydroelectricity; Sustainability